2011
DOI: 10.4021/gr336e
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Hypereosinophilia-Associated Multiple Mass Lesions of Liver Showing Non-Granulomatous Eosinophilic Hepatic Necrosis

Abstract: Hypereosinophilic syndrome (HES) is defined by elevation more than 1.5×109/L of presence of a peripheral blood count, evidence of organ involvement, and exclusion of secondary eosinophilia such as allergic, vasculitis, drugs, or parasite infection and also clonal eosinophilia. We present the HES case with hepatic involvement. The patient is 70-year-old male. He complained fever and back pain. Blood examination showed marked peripheral eosinophilia, elevation of transaminase and biliary enzymes. Multiple irregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…HES presenting as isolated hepatic eosinophilic abscesses is rare. [8,9] The radiological appearance of the eosinophilic abscesses resembled hepatic metastases, which was another unusual finding in our case. [10] HES is an uncommon differential diagnosis in a case of PUO with eosinophilia.…”
Section: Discussionsupporting
confidence: 58%
“…HES presenting as isolated hepatic eosinophilic abscesses is rare. [8,9] The radiological appearance of the eosinophilic abscesses resembled hepatic metastases, which was another unusual finding in our case. [10] HES is an uncommon differential diagnosis in a case of PUO with eosinophilia.…”
Section: Discussionsupporting
confidence: 58%
“…As early as 1947, Samter stated that "numerous observations have established the relation between the presence of disintegrating eosinophilic leukocytes and Charcot-Leyden crystals" [2]. CLCs have been repeatedly described in association with "necrotic" or "damaged" cells ( [21][22][23][24][25], Table 1). In addition, the presence of CLCs in nasal polyps from patients with eosinophilic chronic rhinosinusitis was associated with disease severity [26••].…”
Section: Pathological Features Of Clcsmentioning
confidence: 99%
“…Consequently, we interpreted the eosinophilic liver mass to be a manifestation of hypereosinophilic syndrome. After the liver biopsy, hypereosinophilia was treated by oral administration of prednisolone at an initial dose of 60 mg/day . Two weeks later, a follow‐up contrast‐enhanced CT confirmed that almost all the previously detected tumors had disappeared (Fig.…”
Section: Case Reportmentioning
confidence: 99%
“…Hypereosinophilia can lead to pseudotumors in the liver, most of which are treated by prednisolone. 1 We report a rare case of hypereosinophilia-related liver pseudotumor presumed by the elevation of interleukin (IL)-5, which was produced by T-cell lymphoma detected 10 months after detection of the pseudotumor in the liver.…”
Section: Introductionmentioning
confidence: 99%